Effects of monosaccharides including rare sugars on proliferation of Entamoeba histolytica trophozoites in vitro - Kato, Kentaro; Miura, Mitsumasa; Tachibana, Hiroshi; Tsukamoto, Ikuko (Frontiers in Molecular Biosciences, 2023)
Entamoeba histolytica is a parasitic protozoan with roles in pathogenicity of intestinal amoebiasis. E. histolytica trophozoites lack functional mitochondria and their energy production depends mostly on glycolysis. D-Glucose has a pivotal role in this process and trophozoites store this sugar as glycogen in glycogen granules. Rare sugars, which are defined as sugars present in nature in limited amounts, are of interest as natural low-calorie sweeteners for improving physical conditions of humans. One such rare sugar, D-allose, can be absorbed by a sodium-dependent glucose cotransporter as a substitute for D-glucose, and some rare sugars are known to inhibit growth of cancer cells, Caenorhabditis elegans and Tritrichomonas foetus. Based on these observations, we examined the effects of rare sugars on growth of E. histolytica trophozoites, together with those of D-galactose and D-fructose. The results indicate that treatment with D-allose or D-psicose (D-allulose) alone inhibits proliferation of E. histolytica trophozoites, but that these sugars enhance proliferation of trophozoites in the presence of D-glucose or D-galactose. The trophozoites could take up D-glucose and Dgalactose, but not D-fructose, D-allose or D-psicose. Cell sizes of the trophozoites also differed depending on the culture medium.